Estudo e desenvolvimento de um método de MPPT para sistemas PV, baseado na técnica P&O aplicado a um microinversor do tipo flyback - Rambo , Carlos Eduardo Bizarro (2015)
This work presents the study and development of a modification proposal of the classical MPPT - P&O approach, based on the utilization of the power and voltage derivatives in PV panel terminals. The contribution of this study consists in the employment of the time derivative of voltage that is used to determine converter duty cycle step size instantly. The proposed MPPT approach when compared to the classical P&O, presents some advantages like as: better dynamic response, steady state error reduction and robustness (considering different irradiation and temperature profiles). In order to validate this study, a microinverter prototype based on flyback converter, using this new approach, was implemented aiming to connect PV panels to the mains. Microinverter control strategy was held on Matlab/Simulink® environment in association to a data processing board (DS1104 from dSPACE®).